2020
DOI: 10.1080/14786419.2020.1713122
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid glycosides from the rhizomes of Allium ascalonicum and their anoctamin-1 inhibitory activity

Abstract: Ten triterpenoid glycosides including two new (1 and 2) were isolated from the methanol extract of Allium ascalonicum rhizomes. These compounds were structurally elucidated to be 3β(2), lactifoloside C (3), lactifoloside H (4), randiasaponin IV (5), kudinoside G (6), ilexkudinoside W (7), lactifoloside G (8), kudinoside D (9), and ilexkudinoside T (10) by analyzing their HR-ESI-MS, NMR spectral data and by comparison with those reported in the literature. Compounds 1-10 were evaluated for anoctamin-1 (ANO1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Mai et al isolated ten triterpenoid glycosides from the methanol extract of A. ascalonicum rhizomes, which were evaluated for anoctamin-1 (ANO1) inhibitory activity using yellow fluorescent protein reduction assays. The study revealed that among them, two compounds (compounds 2 and 9, Figure 3G ) showed moderate ANO1 inhibitory percentages ( 83 ).…”
Section: Other Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mai et al isolated ten triterpenoid glycosides from the methanol extract of A. ascalonicum rhizomes, which were evaluated for anoctamin-1 (ANO1) inhibitory activity using yellow fluorescent protein reduction assays. The study revealed that among them, two compounds (compounds 2 and 9, Figure 3G ) showed moderate ANO1 inhibitory percentages ( 83 ).…”
Section: Other Pharmacological Activitiesmentioning
confidence: 99%
“…(G) Chemical structures of compounds 1–10 isolated from shallot screened for anoctamin inhibitory capacity. Compounds 2 and 9 exerted the highest anoctamin inhibitory potential ( 78 83 ).…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 99%